Hubungan harga minyak dunia dan indeks pasar Indonesia selama isu geopolitik - Ferdhyo Natanael Poluan; Gabriel Yosep Maximilianus Koyongian (Yayasan Widyantara Nawasena Raharja, 2023)
The continuation of world geopolitical issues still tends to have an impact on fluctuations in world oil prices. Such circumstances motivated this study to find out how the world oil price relates to the market index in Indonesia. Observations are made from 1 January 2023 to 30 April 2023 with samples of market indexes in Indonesia and world oil prices. This study finds that market indexes in Indonesia tend to have similar returns even though some indexes are indicated to be negative. In addition, this study also finds that all indexes have less than optimal risk reward. The main finding of this study is that changes in world oil prices tend not to be followed by changes in market indexes in Indonesia.